Discordance of the 2011 Criminal Procedure Code of Serbia with other Regulations - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Abstract: The article points to the discordance of the new 2011 CPC with other regulations of our judicial system: The Constitution, practices of the European Court of Human Rights, Criminal Code, Law on Public Prosecution, Law on Police, Law on Contracts and Torts. On the other hand, the laws which have not yet been terminologically or essentially harmonized with the new CPC are presented. All these are sources of discord in our legal system and require introducing changes to the CPC. Keywords: Criminal Procedure Code, Constitution, Criminal Code, Law on Public Prosecution